2002
DOI: 10.1590/s0037-86822002000200004
|View full text |Cite
|
Sign up to set email alerts
|

Influência da hidrocortisona no desenvolvimento do Schistosoma mansoni em Biomphalaria glabrata

Abstract: The effect of hydrocortisone on the development of BH strain of S. mansoni in B. glabrata snails is evaluated. Snails in a randomly chosen group were submitted to hydrocortisone during four days. In the second day of hydrocortisone exposure, the snails were exposed, each, to ten S. mansoni miracidia. Another group, not treated with hydrocortisone, was exposed to miracidia and observed in the same manner. Various items of data were observed: the infection rate, survival time, prepatent period and total number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…These data are in agreement with observation of Serrano et al (2002) who described an increased number of cercariae released by mollusks treated with hydrocortisone.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These data are in agreement with observation of Serrano et al (2002) who described an increased number of cercariae released by mollusks treated with hydrocortisone.…”
Section: Discussionsupporting
confidence: 93%
“…Cercarial shedding was not examined in this experiment but, in a previous study (Serrano et al 2002), we observed more cercarial shedding in mollusks treated with hydrocortisone. Thus in snails treated with hydrocortisone, a total of 69,519 cercariaes was obtained, whereas in untreated mollusks, only 2,514 larva were obtained.…”
Section: Time After Infection (H) No Granulocytes/mmmentioning
confidence: 76%
See 1 more Smart Citation
“…Similar observations were noticed by Sharaf El-Din et al 2004using the herbicide dithiopyridine carboxylic acid, by Mahmoud (2006) using the insecticides: regent and mimic, by Abdel Raouf (2007) using the insecticide, by Esmaeil (2009) using the fungicide. However, Serrano et al (2002) reported that Biomphalaria glabrata snails exposed to hydrocortisone had long survival periods than control group.…”
Section: Discussionmentioning
confidence: 95%
“…Two experimental groups consisting of 52 mollusks each were studied: group A comprised infected mollusks not treated with hydrocortisone and group B infected mollusks treated with hydrocortisone 17 . The snails of both groups were infected on the second day of hydrocortisone treatment and in group A by exposing each snail to 10 miracidia of S. mansoni strain BH.…”
Section: Methodsmentioning
confidence: 99%